Faktor Penentu Minat Beli Konsumen Melalui E-Commerce Berbasis Marketplace - Putri, Solehatin Ika; Yulianti, Eka; Saputra, Galih Ginanjar; Ningrum, Harini Fajar (Jurnal Ilmiah Poli Bisnis, 2022)
This study aims to determine the determinants of consumer buying interest through marketplace Shopee, Tokopedia and Lazada by adopting interest indicators are transactional interest, referential interest, preferential interest and exploratory interest. Based on these four indicators, the indicators that most influence consumer buying interest from each marketplace are determined. The survey method is used through data from online questionnaires distributed to 300 marketplace users. Data analysis using Structural Equation Modeling Warp Partial Least Square (SEM Warp PLS) 7.0 application. The results in this study are that transactional interest, referential interest, preferential interest and exploratory interest have an effect either partially or simultaneously on buying interest through Shopee, Tokopedia and Lazada. Buying interest using Shopee marketplace is most influenced by preferential interest. While buying interest using Tokopedia's marketplace is most influenced by referential interest. As for buying interest using marketplace Lazada, the value of the biggest influence is from transactional interest.